The epistle to the Romans a complete analysis of Romans with annotations - Gaebelein, Arno Clemens, 1861-1945 (New York, NY "Our Hope", 1916)
Includes bibliographical references incl Brethren writers, JND, Pridham, Grant.
Donated by Mrs J. McNaught.
Keywords: Bible. N.T. Romans -- commentaries